PRELIMINARY STUDY ON THE PALM FLORA OF THE LORE LINDU NATIONAL PARK, CENTRAL SULAWESI, INDONESIA - JOHANIS P MOGEA (SEAMEO BIOTROP, 2002)
The population size, structure, and composition of the palm flora in a 1350 m by 20 m rectangular plot in Gunung Potong and a 1500 m by 20 m rectangular plot in Tongoa were measured. The total palm species from both plots numbered 33 represented by 8 genera. Eight species, namely Calamus omatus var. celebicus, Pinanga caesia, Arenga pinnata, Daemonorops sp.3. Calamus didymocarpus. Calamus sp.4 (rapid spines), Caryota mitis, andAreca vestiaria have relatively high frequency values ranging from 5.46% to 10.66%. In addition, palm specimens previously collected from the park were examined at Herbarium Bogoriense to set up a preliminary checklist. So far, the national park is recorded as having 48 palm species represented by 11 genera which give figures of about 68% species and 58% genera of the total native Sulawesi palm flora. Though the number of endemic palms in Sulawesi is high (72%), namely 51 out of total native 71 species, only two species are locally endemic to Central Sulawesi namely Gronophyllum sarasinorum and Pinanga sp. nov. 1 (longirachilla). So far only the latter species is endemic to the national park. Key words: palm diversity/Lore Lindu National Park/Sulawesi/Indonesia/endemic species